Operários chineses em Moçambique. O engajamento de trabalhadores sob contrato no Império português (1857-1859)1 - Gonçalves, Paulo Cesar [UNESP] (Associação Nacional de História - ANPUH, 2021)
At the end of the 1850s, Lisbon conceived the employment of Chinese workers, emigrants from Macau, in services considered specialized (bricklayers, blacksmiths, carpenters, copper workers and stone chippers), in the province of Mozambique, by the system of indentured labor. Even without consulting any authority in those localities about its convenience, the initiative produced a series of documents, which transited vertically between the metropolis and the colonies. This documentation makes it possible to identify a pioneering movement of indentured labor within the limits of the Portuguese empire, in the wake of the growing flow of this type of labor (especially of Chinese and Indian men) in the Indian and Atlantic worlds. Moreover, the documented dispute between these workers and the Mozambican government over the performance and remuneration of services also makes it possible to identify the agency of the Chinese recruits in defending their contractual rights.

No final da década de 1850, Lisboa concebeu o emprego de trabalhadores chineses, emigrados de Macau, em serviços considerados especializados (pedreiros, ferreiros, carpinteiros, cobreiros e picadores de pedra), na província de Moçambique, pelo sistema de trabalho sob contrato. Mesmo sem consultar nenhuma autoridade daquelas localidades sobre sua conveniência, a iniciativa produziu uma série de documentos, que transitou de forma vertical entre a metrópole e as colônias. Essa documentação permite identificar um movimento pioneiro de trabalhadores sob contrato dentro dos limites do império português, na esteira do crescente fluxo desse tipo de mão de obra (sobretudo de chineses e indianos) nos mundos Índico e Atlântico. Por outro lado, a documentada disputa entre esses trabalhadores e o governo de Moçambique, sobre a execução e a remuneração dos serviços, também possibilita identificar a agência dos chineses recrutados na defesa de seus direitos registrados em contrato.
Chinese Workers in Mozambique. The Engagement of Indentured Laborers in the Portuguese Empire (1857-1859)
Keywords: Indentured labor; Chinese emigration; Portuguese Empire; Trabalho sob contrato; Emigração chinesa; Império português